Individual Differences in Human Development - Lanjar Mustikaningwang; Faiz Badridduja; Eva Latipah (Jurnal Al-Hikam, 2022)
article discussed four main topics, where the results of observations in previous research are then connected with educational issues that occur today. The topic of observation is as follows: the role of the genome in the evolution of uniquely human traits occurs dynamically, the relationship between the genome, brain, and sub-sections related to cognition, attempts to associate cognition in the genome, correspondence between a particular level of behavioral complexity and the mechanisms by which the genetic system regulates both, genome and its role in education. The research method in this article is literature review in part one at Innovations in Educational Psychology book edited by David D. Preiss and Robert J. Stenberg as the primary source and other supporting literature as secondary sources. The results of this study reveal that the genome has an important benefit for education, although not directly but can better understand the nature and degree of flexibility of individual differences in the classroom. Keyword: Individual Differences, Human Development, Role of Genom